2015
DOI: 10.1016/j.jjcc.2015.02.015
|View full text |Cite
|
Sign up to set email alerts
|

B-type natriuretic peptide response and reverse left ventricular remodeling after surgical correction of functional mitral regurgitation in patients with advanced cardiomyopathy

Abstract: There may be a significant association between LV reverse remodeling and plasma BNP change after RMA. Furthermore, LV end-systolic myocardial stress may be the key mechanical stimulus influencing plasma BNP after surgical correction for functional MR. Whether these favorable BNP responses and reverse remodeling can predict improved survival requires further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
(47 reference statements)
2
12
0
Order By: Relevance
“…However, as for MV annuloplasty, which provides symptomatic improvement without proven impact on mortality [25][26][27], a randomized prospective trial is necessary for definitive proof. Due to the spreading use of MC therapy such studies are difficult to implement.…”
Section: Discussionmentioning
confidence: 99%
“…However, as for MV annuloplasty, which provides symptomatic improvement without proven impact on mortality [25][26][27], a randomized prospective trial is necessary for definitive proof. Due to the spreading use of MC therapy such studies are difficult to implement.…”
Section: Discussionmentioning
confidence: 99%
“…This outcome may be attributable to the phenomenon known as LV reverse remodeling (LV-RR), which is characterized by an increase in the pump function and a decrease in the LV dimension [7]. LV-RR predicts heart failure staging, exercise performance, and independently, the long-term prognosis of patients with idiopathic DCM [8][9][10][11][12]. Therefore, the predicted LV-RR could be used to stratify patients with latent myocardial damage.…”
Section: Introductionmentioning
confidence: 99%
“…(24) Several other markers of adverse LV remodelling have been studied in patients with valvular heart disease and heart failure in including ST2, cytokines, markers of apoptosis (FAS and FAS ligand) and the MMPs and their inhibitors. (25)(26)(27)(28)(29)(30)(31)(32) Here we have shown that there is a poor correlation between the tissue gene expression levels of several of these markers of adverse LV remodelling in patients with CPMR and the serum levels of these markers sampled at the same time.…”
Section: Discussionmentioning
confidence: 75%